2021
DOI: 10.1002/jcp.30422
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial integrin β4‐deficiency exacerbates lipopolysaccharide‐induced acute lung injury

Abstract: Airway epithelial cells, the first barrier of the respiratory tract, play an indispensable role in innate immunity. Integrin β4 (ITGB4) is a structural adhesion molecule that is involved in the pathological progression of acute inflammatory diseases and is downregulated in asthmatic patients. Research has shown that endothelial ITGB4 has proinflammatory properties in acute lung injury (ALI). However, the role of epithelial ITGB4 in a murine ALI model is still unknown. This study investigated the role of ITGB4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…It has been reported that deleting β1 integrin in lung epithelium beginning at E10.5 results in abnormal lung development with a 100% fatality rate at the age of 16 weeks 12 . Based on our observation, knockout of ITGB4 in airway epithelial cells did not affect the overall survival rate; besides, in our previous research, we observed that after LPS treatment, the mRNA expression of anti‐inflammatory factors, including IL‐10 and ARGA‐1, was significantly reduced in the lung tissue of β4 ccsp.cre mice compared with wild‐type mice 48 . Under the stimulation of HDM, it is more likely for β4 ccsp.cre mice to acquire airway hyper‐responsiveness and asthma than wild‐type mice 39 .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been reported that deleting β1 integrin in lung epithelium beginning at E10.5 results in abnormal lung development with a 100% fatality rate at the age of 16 weeks 12 . Based on our observation, knockout of ITGB4 in airway epithelial cells did not affect the overall survival rate; besides, in our previous research, we observed that after LPS treatment, the mRNA expression of anti‐inflammatory factors, including IL‐10 and ARGA‐1, was significantly reduced in the lung tissue of β4 ccsp.cre mice compared with wild‐type mice 48 . Under the stimulation of HDM, it is more likely for β4 ccsp.cre mice to acquire airway hyper‐responsiveness and asthma than wild‐type mice 39 .…”
Section: Discussionsupporting
confidence: 50%
“… 12 Based on our observation, knockout of ITGB4 in airway epithelial cells did not affect the overall survival rate; besides, in our previous research, we observed that after LPS treatment, the mRNA expression of anti‐inflammatory factors, including IL‐10 and ARGA‐1, was significantly reduced in the lung tissue of β4 ccsp.cre mice compared with wild‐type mice. 48 Under the stimulation of HDM, it is more likely for β4 ccsp.cre mice to acquire airway hyper‐responsiveness and asthma than wild‐type mice. 39 These results suggest a different role of β4 than β1 in lung development.…”
Section: Discussionmentioning
confidence: 99%
“…Genes and biological processes involved in fibrosis were exclusively enriched by PDGF-BB in NHDF. For example, PDGF-BB decreased ITGB4 expression, a signature that is associated with enhanced lipopolysaccharide-induced inflammation ( 38 ). GRPR is the G protein-coupled receptor that binds to gastrin-releasing peptide (GRP).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 1,473 DE genes that are unique to ["PDGF-BB vs VC" in siCtr NHDF] and thus considered to be driven by PDGF-BB through MCHR1 (Supplementary Table 6). Gastrin releasing peptide receptor (GRPR) (log2FC = 4.843; q = 0.00689), integrin subunit beta (ITGB) 4 (log2FC = -5.015; q = 0.00014), and vitronectin (VTN) (log2FC = -4.901; q = 0.00029) were in the list of DE genes (Supplementary Table 6), all genes reported to be associated with fibrosis or inflammation (37)(38)(39).…”
Section: Genes Regulated By Pdgf-bb Via Mchr1mentioning
confidence: 99%
“… 37 Overexpressed MMP12 mRNA may promote the progression and metastasis of ESCA, LIHC, and LUSC and is associated with a poor prognosis in cancer patients. 25 , 38 , 39 Additionally, a high expression of MMP12 mRNA in LUAD promotes lymph node metastasis. 12 Similarly, our study detected that MMP12 is differently expressed in various cancers and that MMP12 is associated with patients’ cancer status and prognosis in several cancers.…”
Section: Discussionmentioning
confidence: 99%